2007
DOI: 10.1007/s10551-007-9529-7
|View full text |Cite
|
Sign up to set email alerts
|

Whistle-Blowing and Morality

Abstract: business ethics, code of ethics, duty, engineering ethics, moral luck, moral obligation,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
13

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(49 citation statements)
references
References 14 publications
0
36
0
13
Order By: Relevance
“…The major assumptions or views on the motivations of whistleblowers that have been adopted by previous studies (usually scenarios) include morality, cost‐benefit calculations, and emotion. Many previous studies (Avakian & Roberts, ; Bouville, ; Grant, ; Hoffman & Schwartz, ) have explained whistleblowing as stemming from high moral motives. Many other studies (e.g., Miceli et al, ) have identified cost‐benefit analysis as the underlying motive in the whistleblowing decision‐making process.…”
Section: Literature Reviewmentioning
confidence: 98%
See 1 more Smart Citation
“…The major assumptions or views on the motivations of whistleblowers that have been adopted by previous studies (usually scenarios) include morality, cost‐benefit calculations, and emotion. Many previous studies (Avakian & Roberts, ; Bouville, ; Grant, ; Hoffman & Schwartz, ) have explained whistleblowing as stemming from high moral motives. Many other studies (e.g., Miceli et al, ) have identified cost‐benefit analysis as the underlying motive in the whistleblowing decision‐making process.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Most previous studies have explained external whistleblowing as an act by people who are highly committed to morality (Bouville, ; Jos, Tompkins, & Hays, ), resulting from normative judgment (Bouville, ; Hoffman & Schwartz, ). The stereotypical public image of an external whistleblower has also been that of the moral hero with unflinching courage who reacted in the face of injustice or danger to the public.…”
Section: Introductionmentioning
confidence: 99%
“…yang Mempengaruhi Minat Whistle-blowing Bouville (2007) mendefinisikan whistleblowing sebagai tindakan, dari seorang pegawai (atau mantan pegawai), untuk mengungkap apa yang ia percaya sebagai perilaku ilegal atau tidak etis kepada manajemen yang lebih tinggi/manajemen puncak (internal whistle-blowing) atau kepada otoritas/pihak berwenang di luar organisasi maupun kepada publik (external whistle-blowing). Banyak penelitian yang telah dilakukan guna mencari faktor-faktor yang mempengaruhi seseorang untuk melakukan whistle-blowing dengan menggunakan minat whistle-blowing sebagai proxy-nya.…”
Section: Faktorunclassified
“…However, when the disclosure is required by the law or prompted by the order of government agencies, the report or information of a whistleblower is not considered as a betrayal. In USA, for instance, there is no case that a whistleblower is considered a betrayal, especially when the organization or the company makes an illegal action (Bouville 2008). …”
Section: Theoretical Framework and Hypo-thesesmentioning
confidence: 99%
“…For that reason, the stakeholders and the internal auditor can identify the bad and poor behavior in which an internal auditor should act with partiality to the public interest by acting as a whistleblower (Bouville 2008). In this case, the internal auditor must be a hero of the stakeholders (Verschoor 2003).…”
Section: The Role Of Internal Auditor As Whistleblowermentioning
confidence: 99%